Lugar de mulher é onde ela quiser! Construção feminina e a política de cotas para mulheres no Brasil - Dunder, Juliana Silva (2018)
The present dissertation proposes to investigate the construction of the social role of women, while aiming to evaluate the situation regarding their political participation in contemporary times, especially in Brazil, with the arrival of the quota policy for women. Based on a historical analysis, more specifically the search for the framework that segregated the spaces of action of human beings, the path taken leads to the understanding of the need for instruments, including positive discrimination for women, as an aid in repairing the inequality framework installed around the world. Using the instruments that made it possible for women to be recognized as holders of rights and duties, there is a contemporaneity where women in political space have hardly changed during the walk, not even with the creation of a system of quotas The analysis of national data, interspersed with data from Argentina, confirms the failure of quotas in Brazil, and is therefore an instrument that insufficiently fosters the occupation of the political space by women, but does not generate significant effects.